Schaum's A-Z mathematics - Berry, J. S., (John Stephen), 1947- (New York : McGraw-Hill, 2003)
Presents explanatory overviews of over six hundred alphabetized mathematical topics, discussing formulas, rules, proofs, and equations and providing more than two hundred examples of how to answer short examination questions. Covers such terms as "cosine rule," "interquartile range (IQR)," and "position vector.".
Rev. ed. of: The complete A-Z mathematics handbook. 2nd ed. c2000.
Young Adult
Keywords: Mathematics -- Handbooks, manuals, etc; Mathematics -- Handbooks, manuals, etc